Formulation and evaluation of glimepiride solid dispersion tablets - Gill, Bhawandeep; Kaur, Tejvir; Kumar, Sandeep; Gupta, G D (Asian Journal of Pharmaceutics (AJP), 2014)
Glimepiride (GMP) is poorly water soluble drug, so solubility is the main constraint for oral its bioavailability. An attempt has been made to increase the solubility of this model drug by formulating solid dispersion (SD) using Poloxamer 188(PXM 188) as polymer and then formulating SDs tablets of the best formulation of SDs. Tablet formulations were prepared by direct compression technique using superdisintegrant croscarmellose sodium in different concentrations. SDs were evaluated for XRD, SEM, in vitro dissolution profiles, and dissolution efficiency, and developed tablet formulations were evaluated for various pharmaceutical characteristics viz. hardness, % friability, weight variation, drug content, disintegration time, in vitro dissolution profiles, and dissolution efficiency. Among different formulations of SDs, SD containing drug is to polymer ratio 1 : 4 gives best dissolution profile and dissolution efficiency and among tablet formulations, formulations containing 5% croscarmellose sodium gives best disintegration and dissolution profiles compared with other formulations. Results showed that poloxamer is a promising polymer for enhancing the solubility of GMP.